Post-Triple Talaq Reconciliation in the Shāfiʿī Perspective: A Case Study of Koto Baringin, Mandailing Natal - Helmida Yanti; Ramadhan Syahmedi Siregar (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
Reports of reconciliation after triple talaq persist in some Indonesian communities due to misconceptions about divorce status, the scope of reconciliation, and family-law pathways. This article examines post-triple talaq reconciliation through the Shāfiʿī doctrinal lens and Indonesian positive law (the Compilation of Islamic Law/KHI and the Marriage Law) using a qualitative socio-legal case study in Koto Baringin, Mandailing Natal. Data were gathered via in-depth interviews with religious leaders, village/KUA officers, and affected couples, complemented by observation and document review, and analyzed thematically with source/method triangulation. Findings show three recurrent patterns: informal cohabitation without a prior court dissolution or a lawful route to reconciliation; reliance on community leaders’ social legitimacy in place of legal verification; and persistent confusion about “triple talaq at once” and its consequences. In the Mazhab Shāfiʿī , triple talaq triggers baʾīn kubrā; reconciliation is invalid until tahallul occurs through a genuine, non-sham subsequent marriage (nikāḥ taḥlīl is prohibited). Under Indonesian law, divorce is valid only through the Religious Court and reconciliation must follow prescribed procedures and registration. Non-compliance produces legal uncertainty regarding marital status, children’s civil documentation, inheritance, and access to state services. The study recommends strengthening family-law literacy, intensifying KUA counseling, and strict adherence to court procedure and civil registration.